Chapter 8 Linguistic inclusion and exclusion on Abu Dhabi coronavirus signage - Hopkyns, Sarah (Taylor & Francis, 2022)
The linguistic ecology of the United Arab Emirates (UAE) is characterized by diversity. While effective communication in multilingual contexts is important during ordinary times, it becomes especially vital during a crisis such as the Coronavirus pandemic. This chapter explores linguistic inclusion and exclusion on Abu Dhabi Coronavirus safety signage. An ethnographic approach to linguistic landscaping is taken through the analysis of languages and semiotic resources used on signage in community and leisure spaces. Findings revealed a prevalence of monolingual and bilingual signage which favoured the nation's official language, Arabic, and the nation's de facto lingua franca, English. Whereas examples of effective trilingual signage were found, these were the exception rather than the norm. The chapter argues that greater linguistic inclusion of languages other than English and Arabic is needed to reflect Abu Dhabi's multilingual ecology and ensure safety messages are more accessible. Raising awareness of linguistic diversity in society as well as implementing translation drives are suggested as ways to promote greater inclusion of third languages on signage during the pandemic period and beyond, as well as supporting a greater sense of belonging for linguistic minorities.